Comparación de la dieta de dos especies de rapaces ornitofagas, el halcón perdiguero (falco femoralis) y el vari (circus cinereus), en la región pampeana de Argentina - Baladrón, Alejandro V. (2012)
We studied the diet and hunting activity of two bird-eating raptors, the Aplomado Falcon (Falco femoralis) and the Cinereous Harrier (Circus cinereus), in Mar Chiquita Biosphere Reserve, Argentina. Prey was identified by analyzing pellets collected during December 2005. The Cinereous Harrier showed a higher consumption of birds than the Aplomado Falcon (92,3% vs 67,9% of total prey, respectively), and a reverse tendency was observed for the biomass contribution (26% vs 88%). In addition, these raptors showed differences in hunting techniques: the Aplomado Falcon used a sit-and-wait strategy, whereas the Cinereous Harrier used an active-search strategy. Our results suggest that both factors, the use of different prey and hunting modes, could be important for trophic niche segregation between these two bird-eating raptors.